2010
DOI: 10.1039/c000988a
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark calculations of water–acene interaction energies: Extrapolation to the water–graphene limit and assessment of dispersion–corrected DFT methods

Abstract: In a previous study (J. Phys. Chem. C, 2009, 113, 10242-10248) we used density functional theory based symmetry-adapted perturbation theory (DFT-SAPT) calculations of water interacting with benzene (C(6)H(6)), coronene (C(24)H(12)), and circumcoronene (C(54)H(18)) to estimate the interaction energy between a water molecule and a graphene sheet. The present study extends this earlier work by use of a more realistic geometry with the water molecule oriented perpendicular to the acene with both hydrogen atoms poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
154
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(168 citation statements)
references
References 53 publications
13
154
1
Order By: Relevance
“…This is a small number of rings for modeling a finite graphene surface. However, recent theoretical calculations indicated that this size of graphene sheet can reasonably represent the electronic states of the graphene system [18][19][20][21]. Therefore, the present calculations would provide useful information on the ternary interaction system.…”
Section: Discussionmentioning
confidence: 99%
“…This is a small number of rings for modeling a finite graphene surface. However, recent theoretical calculations indicated that this size of graphene sheet can reasonably represent the electronic states of the graphene system [18][19][20][21]. Therefore, the present calculations would provide useful information on the ternary interaction system.…”
Section: Discussionmentioning
confidence: 99%
“…It is also very encouraging that condensed phase reference systems are beginning to emerge, such as ice, LiH, water on LiH and water on graphene. 63,154,155,[157][158][159][160][161][162][163][164] By tackling these and other reference systems with the widest possible range of techniques we will better understand the limitations of existing dispersion-based DFT approaches, which will aid the development of more efficient and more accurate methods for the simulation of materials in general.…”
Section: Final Remarksmentioning
confidence: 99%
“…[17][18][19] Despite the growing number of studies for water on h-BN [20][21][22] and graphene 15,16,[23][24][25][26][27] there are no direct measurements of adsorption energies for the water monomer, and the theoretical adsorption energies for these systems vary significantly across different high accuracy methods. 25,[27][28][29] One can use smaller model systems for graphene 25,[29][30][31][32] and h-BN, such as benzene and the inorganic counterpart borazine (B 3 N 3 H 6 ), to help understand the interaction with water. With these small molecules, it is possible to use high accuracy methods to calculate benchmark interaction energies and binding conformations, [33][34][35][36][37] that would otherwise be infeasible for the extended surfaces.…”
Section: Introductionmentioning
confidence: 99%